New pancreatic cancer biomarkers eIF1, eIF2D, eIF3C and eIF6 play a major role in translational control in ductal Adenocarcinoma - Golob-Schwarzl, Nicole; Puchas, Philip; Gogg-Kamerer, Margit; Weichert, Wilko; Goeppert, Benjamin; Haybaeck, Johannes (Anticancer research, 2020)
Background/Aim: Pancreatic cancer is one of the deadliest forms of cancer and ranks among the leading causes of cancer-related death worldwide. The most common histological type is ductal adenocarcinoma (PDAC), accounting for approximately 95% of cases. Deregulation of protein synthesis has been found to be closely related to cancer. The rate-limiting step of translation is initiation, which is regulated by a broad range of eukaryotic translation initiation factors (eIFs). Patients and Methods: Human PDAC samples were biochemically analyzed for the expression of various eIF subunits on the protein level (immunohistochemistry, immunoblot analyses) in 174 cases of PDAC in comparison with non-neoplastic pancreatic tissue (n=10). Results: Our investigation revealed a significant down-regulation of four specific eIF subunits, namely eIF1, eIF2D, eIF3C and eIF6. Concomitantly, the protein (immunoblot) levels of eIF1, eIF2D, eIF3C and eIF6 were reduced in PDAC samples as compared with non-neoplastic pancreatic tissue. Conclusion: Members of the eIF family are of relevance in pancreatic tumor biology and may play a major role in translational control in PDAC.